Breaking the glass ceiling helping women overcome the barriers to career progression (London : BBC Training Videos, 1993)
The content of the video is based on interviews with people in both the UK and USA who are either women who have broken the glass ceiling themselves or are experts of some kind who have done study and/or research into the phenomenon of the glass ceiling
Keywords: Women executives; Women employees; Sex discrimination in employment; Sex discrimination against women